BUSINESS MODEL CANVAS VOLKS.Co FACILITY PEKANBARU - Ulfah, Mutia (Komunitas Manajemen Kompetitif, 2018)
Some of the most influential and recent studies in the context of urban economies and creative industries have shown how workers are largely freelance, precarious professionals characterized by a necessity to entertain relationships and manage social capital across their professional network as a decisive source for incoming jobs. They have to develop a self-entrepreneurial ethos and perform self-branding strategies in a highly identitarian, entrepreneurial landscape. In reaction to the new work order, new forms of work emerge in various countries in the world including Indonesia, such as the currently popular coworking space. Coworking spaces provide a productive, creative and satisfying work atmosphere, not just for freelancer but also for corporate organization. Volks.co as the first coworking space in Pekanbaru needs to adapted to some circumstances in Pekanbaru. This study try to figure out the ability of Volks.co business strategy by using Business Model Canvas (BMC), SWOT Analysis, IPA Matrix as a tool map to review the business strategy of Volks.co. Furthermore, based on the findings there’s few things need to improve by Volks.co to keep running and growing the business within the industry in the future